Arbitragem nos contratos administrativos: o limite decisório na avaliação das sanções administrativas - Souza, Vinícius Augusto Cipriano Maniçoba de (2021)
The way of administering the State was not always delineated by democratic principles. The structuring of the managerial model of Public Administration gave rise to the approximation of the administered and the State's self-assessment in its role in realizing social and economic rights. With this perspective, the construction of this study permeates the entire historical foreshortening of the state administration, inferring its respective evolutionary process and the chain reaction resulting from the anxieties of each moment the effects arising from the process of consensualism that, for its time, it provided opportunities for social participation in decision-making. This prefacial approach allows for a critical examination of the (un)availability of administrative sanctions and their consequent arbitrability. The justification for this is based on the need to scrutinize the legal possibility of implementing the arbitration mechanism in the analysis of acts of the State's disciplinary power, to imprint administrative efficiency on the underlying issue involved, for example, in the administrative contracts that they are paralyzed due to a legal dispute in this regard. And if it is possible to use this mechanism, the analysis would stop at the limit that should be established for the arbitrator in the assessment of administrative sanctions. Timely, this dissertation performs a comparison of the legal nature of the administrative sanction after the innovations arising from Federal Law nº. 12.846/2013 – Anti-Corruption Law – with the intention of demonstrating the availability of these interests and their consequent arbitrability. It is concluded, therefore, that the arbitrator's analysis can be made regarding all the structural aspects that motivate the application of administrative sanctions, except for the limitation that this extrajudicial judgment must adhere to legal criteria in the decisional examination of the submitted question. This research is based on an analysis of specific literature on topics of administrative law, constitutional law, and procedural law, specifically sanctioning administrative law, in addition to the dimensioning of constitutional and infra-constitutional legal norms. The analysis is based on a systemic interpretation of the administrative action of sanctioning, defining it as discretionary and of a business nature.